5-HT1A receptor-dependent control of nigrostriatal dopamine neurotransmission in the pharmacotherapy of Parkinson's disease and schizophrenia. Issue 1 (February 2015) - Haleem, Darakhshan J.
Abstract : Dysfunctions of the basal ganglia are associated with a number of neurological and psychiatric conditions including Parkinson's disease and schizophrenia. Current treatments of these disorders are mostly symptomatic and inadequate, and are often associated with a number of unwanted side-effects. The striatum, the terminal region of the nigrostriatal dopamine pathway, is the main input nucleus of the basal ganglia, and dopamine neurotransmission through the nigrostriatal pathway plays a crucial role in the modulation of basal ganglia output and mediated behaviors. Evidence suggests a role of 5-hydroxytryptamine (5-HT; serotonin)-1A receptors in the modulation of dopamine neurotransmission and in improving pharmacotherapy in schizophrenia and Parkinson's disease. This review concerns the role of 5-HT1A receptors in the modulation of nigrostriatal dopamine neurotransmission, with the aim of providing guidelines for future research to improve pharmacotherapy. The current state of knowledge suggests that drugs simultaneously targeting dopamine D2 and 5-HT1A receptors may improve pharmacotherapy for schizophrenia and Parkinson's disease. Activation of somatodendritic 5-HT1A receptors in the dorsal raphe nucleus has an important role in the alleviation of extrapyramidal symptoms and levodopa-induced dyskinesia induced by antipsychotic treatment. Drugs acting exclusively through dopamine D2 and 5-HT1A receptors are highly needed to validate the potential role of 5-HT1A receptors in improving therapeutics for Parkinson's disease and schizophrenia.